Contesting Sacred Gifts: The Erosion of Waqif’s Rights in a Waqf Dispute in Prabumulih, South Sumatra - Kencana, Ulya; Astina, Ria; Erniwati, Erniwati; Antasari, Rina; Sagita, Diniaria (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2024)
The practice of waqf in South Sumatra society has been going on for a long time and is regulated both in Islamic law and in applicable legislation. However, disputes related to waqf land still occur, such as the case in Prabumulih, South Sumatra, where heirs tried to reclaim property that had been donated as waqf. This article discusses waqf from a legal perspective and analyzes disputes over the withdrawal of waqf assets by heirs within the framework of human rights (HAM). The theory used is the human rights theory, which asserts that the rights of every individual are protected by law, including the rights of the deceased waqif. This study employs a normative-empirical approach: the normative approach is used to examine waqf regulations, while the empirical approach is applied in analyzing the waqf dispute case in Prabumulih. The results of the study show that in Islamic law, differences in the definition of waqf among schools of thought lead to variations in practice in society. Regulations in Indonesia require the registration of waqf land at the Office of Religious Affairs to prevent disputes. From a human rights perspective, the heirs' efforts to withdraw waqf assets are illegal and violate the waqif's human rights, which should remain protected. Praktik wakaf di masyarakat Sumatera Selatan telah berlangsung sejak lama dan telah diatur baik dalam hukum Islam maupun dalam peraturan perundang-undangan yang berlaku. Namun, sengketa terkait tanah wakaf masih terjadi, seperti kasus di Prabumulih, Sumatera Selatan, di mana ahli waris mencoba menarik kembali harta yang telah diwakafkan. Artikel ini membahas wakaf dari sudut pandang hukum serta menganalisis sengketa penarikan harta wakaf oleh ahli waris dalam kerangka hak asasi manusia (HAM). Teori yang digunakan adalah teori HAM, yang menegaskan bahwa hak setiap individu dilindungi oleh hukum, termasuk hak waqif yang telah wafat. Penelitian ini menggunakan pendekatan normatif-empiris: pendekatan normatif digunakan untuk mengkaji regulasi wakaf, sementara pendekatan empiris diterapkan dalam menganalisis kasus sengketa wakaf di Prabumulih. Hasil penelitian menunjukkan bahwa dalam hukum Islam, perbedaan definisi wakaf di antara mazhab menyebabkan variasi dalam praktik di masyarakat. Regulasi di Indonesia mengharuskan pencatatan tanah wakaf di Kantor Urusan Agama guna mencegah terjadinya sengketa. Dari perspektif HAM, upaya ahli waris untuk menarik kembali harta wakaf merupakan tindakan yang melanggar hukum dan mencederai hak asasi waqif yang seharusnya tetap dilindungi.